SUFFIXES OF NOUNS AND ADJECTIVES - Navruzova Farida Nazarovna (Western European Studies, 2024)
The word-formation semantics of action names is considered. The combination of procedural and objective meanings is considered as a phenomenon due to the polysemy of the suffix. Action names that have objective meanings form a transition zone between syntactic and lexical derivation.
Keywords: syntactic and lexical derivation; action names; word-formation affix